A rheometry method to assess the evaporation‐induced mechanical strength development of polymer solutions used for membrane applications. Issue 6 (30th August 2018) - Caicedo‐Casso, Eduard; Sargent, Jessica; Dorin, Rachel M.; Wiesner, Ulrich B.; Phillip, William A.; Boudouris, Bryan W.; Erk, Kendra A.
ABSTRACT: Rotational and oscillatory shear rheometry were used to quantify the flow behavior under minimal and significant solvent evaporation conditions for polymer solutions used to fabricate isoporous asymmetric membranes by the self‐assembly and non‐solvent induced phase separation (SNIPS) method. Three different A‐B‐C triblock terpolymer chemistries of similar molar mass were evaluated: polyisoprene‐ b ‐polystyrene‐ b ‐poly(4‐vinylpyridine) (ISV); polyisoprene‐ b ‐polystyrene‐ b ‐poly( N, N ‐dimethylacrylamide) (ISD); and polyisoprene‐ b ‐polystyrene‐ b ‐poly( tert ‐butyl methacrylate) (ISB). Solvent evaporation resulted in the formation of a viscoelastic film typical of asymmetric membranes. Solution viscosity and film viscoelasticity were strongly dependent on the chemical structure of the triblock terpolymer molecules. A hierarchical magnitude (ISV > ISB > ISD) was observed for both properties, with ISV solutions displaying the greatest solution viscosity, fastest film strength development, and greatest strength magnitude. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47038. Abstract :